2012
DOI: 10.1002/ep.11720
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potential liquid organic fertilizers obtained by alkaline extraction from two‐phase olive‐mill waste composts

Abstract: Two potential liquid fertilizers were produced from two mature “alperujo” composts by using an alkaline extraction (1M KOH at 70°C). The characteristics of the resulting humic‐like substances were compared to those extracted according to the international humic substance society protocol by using elemental analysis, FTIR and fluorescence spectroscopy in both excitation‐emission matrix and synchronous modes. The results obtained confirmed that the hot alkaline extraction dissolved more polymerized compounds, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(60 reference statements)
2
0
0
Order By: Relevance
“…These results suggest that fulvic acid, which has a relatively simple structure in the composting process, is decomposed by mineralization and microbial action simultaneously and that part of the fulvic acid can also form humic acid with higher structural complexity through intermolecular bonding (Bu et al, 2015). The results described above are consistent with the report by (Baddi et al, 2013), which indicated that the composting process is characterized by an increase in the humification degree of DOM. Moreover, the ratio of FLR area to HLR area (A FLR /A HLR ) can be used to characterize DOM transformation during composting.…”
Section: Resultssupporting
confidence: 92%
“…These results suggest that fulvic acid, which has a relatively simple structure in the composting process, is decomposed by mineralization and microbial action simultaneously and that part of the fulvic acid can also form humic acid with higher structural complexity through intermolecular bonding (Bu et al, 2015). The results described above are consistent with the report by (Baddi et al, 2013), which indicated that the composting process is characterized by an increase in the humification degree of DOM. Moreover, the ratio of FLR area to HLR area (A FLR /A HLR ) can be used to characterize DOM transformation during composting.…”
Section: Resultssupporting
confidence: 92%
“…FA and HA were mainly composed of carbon and oxygen elements. The carbon and oxygen contents of FA were 28.99% and 65.37%, respectively, while those of HA were 50.98% and 38.88%, which were consistent with the elemental analysis ratio of HA reported in the previous literature [ 28 , 29 ].…”
Section: Resultssupporting
confidence: 91%